Arsitektur Masjid Jami’Sulthan Ayyub Sanggau - Abdurrahman, M. Kasim (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2014)
This paper seeks to uncover the historical and religious inscriptions on the Mosque of Sulthan Ayyub Sanggau, West Kalimantan. This research used a qualitative research perspective. The Research found that the mosque still retain traditional Islamic architectural style of the main building. It is seen in the conical dome, roof shingle materials used, and mustaka located on the top of the roof of the mosque. The influence of local architectural styles seen in the mosque dominated the paint in yellow and green. The mosque is still storing artifacts as evidence of the triumph of Islam at the time, particularly by maintaining building domes, towers, flagpoles, pulpits, and some other Islamic inscriptions. Keywords: Islamic epigraphy, Masjid, Sulthan Ayyub Paku Negara, Sanggau West Kalimantan.